Garré's Sclerosing Osteomyelitis with Perimandibular Soft Tissue Inflammation and Fistula - Shanmuga Jayanthan, S.; Ganesh, Rajagopal (Indian Journal of Radiology and Imaging, 2021)
Garré's sclerosing osteomyelitis is a form of chronic osteomyelitis that commonly affects children and young adults. Here, we report one such case of Garré's sclerosing osteomyelitis in a 20-year-old female who presented with facial asymmetry and inability to open mouth. On clinical examination, it was bony hard swelling with trismus. History of infected second molar tooth extraction was present. Computed tomography scan showed thickening and sclerosis of the ramus and condylar process of mandible, on right side, with proliferative periostitis. Magnetic resonance imaging showed soft tissue edema and inflammation, in the form of enlargement of right masseter and pterygoid muscles with intramuscular fluid collection. On the basis of history, clinical signs, and imaging features, diagnosis of Garré's osteomyelitis with fascial space infection was made. To our knowledge, very few cases of Garré's osteomyelitis present with superimposed fascial space infection, as it is otherwise a nonsuppurative condition. Fistula formation is a very rare incidence as it is seen in our case.
Keywords: CT proliferative periostitis; MRI Garré's osteomyelitis; suppurative osteomyelitis